Efficient treatment of non-grey radiative properties of particles and gases in modelling of radiative heat transfer in combustion environments. (May 2017) - Johansson, Robert
Highlights: Spectral modelling of radiative heat transfer in combustion environments. Evaluation of approximate radiative property models. Proposal of efficient models for gas and particle radiative properties. Abstract: Approximate models for calculation of the radiative properties of gases and particles in combustion chambers are evaluated. Detailed spectral models, in the form of a narrow-band model and Mie-theory, are used as reference and several test conditions are investigated. The approximate models include a grey and a non-grey formulation of a weighted-sum-of-grey-gases model for the gas radiation and several grey particle correlations; the optical limit, the anomalous limit and correlations proposed for calculation of radiative properties of combustion particles. Focus is put on the particle properties and simulations with the approximate particle correlations are also compared with simulations based on grey particle properties calculated by a spectral integration of the Mie data. The results show that the proposed particle correlations give errors of the radiative source term and wall flux within 10% when the non-grey WSGG model is used and within 15% when the grey WSGG model is used in conditions where fuel particles are present. These results are comparable to the ones obtained with grey particle properties calculated from the Mie data. Errors for conditions with only ash particles are significantly larger and are also more dependent on the spectral variation of the complex index of refraction of the ash as there are significant variations in reported ash data.